Active dynamic thermography to detect the presence of stenosis in the carotid artery. (May 2020) - Saxena, Ashish; Ng, E.Y.K.; Lim, Soo Teik
Abstract: Unlike passive infrared (IR) thermal imaging/thermography, where no external stimulation is applied, active dynamic thermography (ADT) results in a high contrast thermal image. In ADT, transient thermal images of the skin surface are captured using an IR thermal camera while the skin surface is stimulated externally, followed by a recovery phase. Upon the application of external stimulation, the presence of stenosis in the carotid artery is expected to differ the recovery rate of the external neck skin surface from the case with no stenosis. In this prospective study, using an external cooling stimulation, the ADT procedure was performed on a total of 54 (N) samples (C: N = 19, 0% stenosis; D1: N = 17, 10%–29% stenosis; D2: N = 18, ≥30% stenosis using Duplex Ultrasound). Analyzing the ADT sequence with a parameter called tissue activity ratio ( T A R ), the samples were classified using a cut-off value: C versus (D1+D2) and (C + D1) versus D2. As the degree of stenosis increases, the value of the T A R parameter depreciates with a significant difference among the sample groups (C:0.97 ± 0.05, D1:0.80 ± 0.04, D2:0.75 ± 0.02; p < 0.05). Under the two classification scenarios, classification accuracies of 90% and 85%, respectively, were achieved. This study suggests the potential of screening CAS with the proposed ADT procedure. Graphical abstract: Image 1 Highlights: External cooling-based active dynamic thermography (ADT) was performed. Presence of carotid artery stenosis (CAS) differs the skin recovery. Single thermal image was extracted from ADT sequence using quantitative parameter. Quantitative parameter was defined by the ratio of rate of rewarming to cooling. Cut-off value-based binary classification model was used to test CAS prediction.